Stigma, Secrecy and Race: An Empirical Examination of Black and White Incarcerated Men - Winnick, Terri A. (American journal of criminal justice, 2009)
In modified labeling theory (MLT) persons with disreputable labels anticipate stigmatization and adopt coping strategies, among them being secretive. We examine endorsement of secrecy among black and white incarcerated men, focusing on race differences. We find whites are significantly more secretive than blacks about ex-convict status. Race effects are net of other predictors, including devaluation/discrimination beliefs, ex-convict friends, religious affiliation and perceived difficulty finding a job. Split sample analyses show only devaluation/discrimination beliefs predict secrecy among blacks. Thus, white privilege may play a role in stigma management. Since ex-convict status suspends white privilege, secrecy may help white ex-convicts maintain their advantage, especially in the job market. Secrecy is also more successfully enacted among whites, who are not usually assumed to have a criminal record. While black convicts expect their label to prompt rejection, for them racial stigma may supersede ex-convict stigma, making management of the latter status less compelling.